2022
DOI: 10.1002/chem.202103931
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Synthesis of Tertiary Allylic Amines by Titanium‐Catalyzed Hydroaminoalkylation of Alkynes with Tertiary Amines

Abstract: Intermolecular hydroaminoalkylation reactions of symmetrical and unsymmetrical alkynes with tertiary amines take place in the presence of catalytic amounts of TiBn 4 , Ph 3 C[B(C 6 F 5 ) 4 ], and a sterically demanding aminopyridinato ligand precursor. The resulting products, synthetically and pharmaceutically useful tertiary β,γ-disubstituted allylic amines, are formed in convincing yields and with excellent stereoselectivity. Particularly promising for future applications is the fact that even the industrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…While significant advances in the field of alkene hydroaminoalkylation catalysis with early transition-metal complexes have been realized, catalytic hydroaminoalkylation of alkyne substrates has only been recently reported. Stoichiometric alkyne hydroaminoalkylation was pioneered by the Buchwald group and further developed by Norton and others (Scheme ). ,,, In these reports, insertion of alkynes into the Zr–C bond of zirconaaziridine complexes, supported by cyclopentadienyl-derived ligands (e.g., A ), resulted in the formation of isolable five-membered metallacyclic complexes ( B ).…”
Section: 3-(no) Zirconium Complexes For Hydrofunctionalization Reactionsmentioning
confidence: 99%
“…While significant advances in the field of alkene hydroaminoalkylation catalysis with early transition-metal complexes have been realized, catalytic hydroaminoalkylation of alkyne substrates has only been recently reported. Stoichiometric alkyne hydroaminoalkylation was pioneered by the Buchwald group and further developed by Norton and others (Scheme ). ,,, In these reports, insertion of alkynes into the Zr–C bond of zirconaaziridine complexes, supported by cyclopentadienyl-derived ligands (e.g., A ), resulted in the formation of isolable five-membered metallacyclic complexes ( B ).…”
Section: 3-(no) Zirconium Complexes For Hydrofunctionalization Reactionsmentioning
confidence: 99%
“…Finally, we tested several other homoleptic early transition metal alkyl complexes that are known hydroaminoalkylation catalysts, such as Ti(CH2SiMe3)4 and ZrBn4, 22,27,65 With L1 ligand, none of them gave no observable photo reactivity (Entry 11-13), suggesting the unique reactivity of Ta complex under photonic excitation.…”
Section: Early Transition Metal Complex Reactivity Screeningmentioning
confidence: 99%
“…Also, less toxic and less expensive early-transition metals (ETM) from groups 3, 4 and 5, including earth abundant metals like titanium can be used as catalysts. [22][23][24][25][26] In recent years this strategy has proven to be an efficient, thermally promoted reaction. However, like many other C-H functionalization reactions, this transformation often requires very high reaction temperatures of up to 180 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Early transition-metal-catalyzed hydroaminoalkylation of unsaturated substrates other than alkenes has recently been shown to expand the scope of nitrogen-containing molecules that can be synthesized through this C–C bond-forming strategy. For example, intermolecular hydroaminoalkylation of allenes enables the formation of allylic amines, with a homoallylic amine isomer as a minor side-product. , To assemble allylic amines in a more selective manner and from commercially available feedstocks, the catalytic hydroaminoalkylation of alkynes was disclosed by our group using a bis(ureate)-supported zirconium catalyst and by the Doye group using titanium-based catalysts. , Preliminary studies of these catalyst systems have suggested that alkyne hydroaminoalkylation proceeds through an analogous mechanism to that of the alkene variant (Scheme b). , …”
Section: Introductionmentioning
confidence: 99%
“…23,24 To assemble allylic amines in a more selective manner and from commercially available feedstocks, the catalytic hydroaminoal-kylation of alkynes was disclosed by our group using a bis(ureate)-supported zirconium catalyst 25 and by the Doye group using titanium-based catalysts. 26,27 Preliminary studies of these catalyst systems have suggested that alkyne hydroaminoalkylation proceeds through an analogous mechanism to that of the alkene variant (Scheme 1b). 29,30 In this mechanism, a catalytically active metallaaziridine intermediate A is formed upon N−H/C−H activation from the corresponding bis(amido) precatalyst (Scheme 1b).…”
Section: ■ Introductionmentioning
confidence: 99%